2008
DOI: 10.1111/j.1471-4159.2008.05327.x
|View full text |Cite
|
Sign up to set email alerts
|

DJ‐1‐binding compounds prevent oxidative stress‐induced cell death and movement defect in Parkinson’s disease model rats

Abstract: Parkinson's disease (PD) is caused by dopaminergic cell death, and genetic and environmental factors are thought to affect the onset of PD. These factors lead to oxidative stress, mitochondrial dysfunction and impairment of the protein degradation system, resulting in cell death. Although a precursor of dopamine and inhibitors of dopamine degradation have been used for PD therapy, cell death progresses during treatment. Identification of compounds or proteins that inhibit oxidative stress-induced neuronal cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 33 publications
1
83
0
Order By: Relevance
“…In 19), FLAG-DJ-1, endogenous DJ-1, and ␤-actin were analyzed as described in the legends of Fig. 1, E and F, and Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 19), FLAG-DJ-1, endogenous DJ-1, and ␤-actin were analyzed as described in the legends of Fig. 1, E and F, and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…and DDC-To examine the effects of DJ-1 on expression and activity of TH and DDC, human neuroblastoma SH-SY5Y cells, in which the DJ-1 gene was knocked down, were established by transfection of a vector containing short hairpin RNA targeting human DJ-1, as described previously (19), and were named "DJ-1 knockdown cells" (19). SH-SY5Y cells harboring the vector without short hairpin RNA were also established and named "Vector cells."…”
Section: Effects Of Dj-1 Knockdown On Expression and Activity Of Thmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds inhibit excess oxidation of C106 of DJ-1 and maintain the reduced form DJ-1, thereby inhibiting oxidative stress-induced neuronal cell death and mitigating locomotion defect in mouse and rat PD models concomitantly with increased TH and mitochondrial complex I activities. These compounds are able to penetrate the BBB 192,195,196) and are also effective in stroke model rats. 197) Protective activities of DJ-1-binding compounds are lost in DJ-1-knockdown or -knockout cells and in DJ-1-knockout mice, indicating the DJ-1-dependency of compounds.…”
Section: Identification Of Dj-1-binding Compounds and Their Applicatimentioning
confidence: 99%
“…We first clarified the X-ray crystal structure of DJ-1 and found that there is a pocket around C106 of DJ-1. 108) After in silico screening for DJ-1-binding compounds using a university compound library and Zinc library, various compounds, including compound B/UCP0054278, compound A/ UCP0045037 and compound-23, were obtained [192][193][194][195] (Fig. 7).…”
Section: Identification Of Dj-1-binding Compounds and Their Applicatimentioning
confidence: 99%